Characterization of Antimicrobial Bacteriocin Produced by Bacillus cereus SS28 Isolates from Budu, a Traditionally Fermented Fish Product of West Sumatera - YUSRA YUSRA; FAUZAN AZIMA; NOVELINA NOVELINA; PERIADNADI PERIADNADI (Microbiology Indonesia, 2014)
Bacillus cereus SS28 isolated from budu, a fermented fish product from West Sumatra, produced antimicrobial compound that had broad spectrum of inhibition against five microorganisms (Escherichia coli, Staphylococcus aureus, Salmonella thypi, Bacillus subtilis, and Listeria monocytogenes). The aims of this research are characterization of Bacillus cereus SS28 antimicrobial activity and observation of its effect to the cellular morphology of Staphylococcus aureus with electron microscope. Antimicrobial compound produced by Bacillus cereus SS28 was stable at pH range between 2 and 11 and to heating at 121 Â°C for 15 min. Maximum antimicrobial activity was expressed at pH 2-3 and 70 Â°C for 45 min. The activity remained after 15 min exposure to UV light. The main changes observed under SEM and TEM were the alteration of Staphylococcus aureus structural cell membrane 48 h after exposure to the antimicrobial compound from Bacillus cereus SS28.